Retributivism has a past : has it a future? - Tonry, Michael H. (Studies in penal theory and philosophy., 2011)
A collection of essays by major figures in punishment theory law, and philosophy that reconsiders the popularity and prospects of retributivism, the notion that punishment is morally justified because people have behaved wrongly.